Egypt, enigmatic civilization: analysis of ‘The Amazing Game of Zamba and his friends: Egypt’ (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2023)
In this article, we propose to carry out a historical and didactic analysis of “El asombroso juego de Zamba y sus amigos: Egipto”, which premiered on the television network PakaPaka in December 2016. The episode starts with a question from Miss Silvia: “Who can tell me on which river the Egyptian civilisation was born and developed?” The amazing team will solve that weekly riddle in a three-level game to save the crowns of Upper and Lower Egypt. Given that the Zamba serie is aimed at children aged 10 and over (many of whom have never been taught about Egyptian society in school) and that this will be their first contact with it, we wonder what knowledge is being conveyed and in what way, what vision of ancient Egypt is being built up in this episode, and what didactic strategies are being used.
Keywords: Egypt; Zamba; historical analysis; didactic strategies